Who perceives lower wages for women to be fair? How perceptions of the fairness of men's and women's wages vary by firm and workplace characteristics - Susanne Strauß; Ole Brüggemann; Julia Lang (University of Konstanz, Cluster of Excellence "The Politics of Inequality", 2024)
Previous research has shown that gender pay gaps are perceived as fair or justified, not only by men but also by women. In this paper we analyse whether this gender bias in the evaluation of fair wages still persists and whether the organizational context has an impact on fairness perceptions. We use unique data from a vignette study that was part of a representative online survey of 5,556 employees in 532 larger firms (> 100 employees) in Germany which are merged to administrative data. This allows us to consider different contextual factors at both the workgroup level and the firm level. In contrast to older studies we find that women tend to evaluate wages of female workers as unfairly too low. Moreover, the perception of (un)fair wages depends on the organizational context. Female supervisors and collective bargaining agreements in firms increase women's awareness for other women's unfairly too low wages, whereas an exchange about wages with co-workers affects the fairness perceptions of both male and female workers.
urn:nbn:de:bsz:352-2-sofyhpevr9ys3
Keywords: 320; Gender inequality; wages; fairness; organizational context; Germany